2017
DOI: 10.3389/fenvs.2017.00018
|View full text |Cite
|
Sign up to set email alerts
|

From Elements to Function: Toward Unifying Ecological Stoichiometry and Trait-Based Ecology

Abstract: The theories developed in ecological stoichiometry (ES) are fundamentally based on traits. Traits directly linked to cell/body stoichiometry, such as nutrient uptake and storage, as well as the associated trade-offs, have the potential to shape ecological interactions such as competition and predation within ecosystems. Further, traits that indirectly influence and are influenced by nutritional requirements, such as cell/body size and growth rate, are tightly linked to organismal stoichiometry. Despite their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 112 publications
(130 reference statements)
5
67
2
Order By: Relevance
“…Our long-term data showed that the phytoplankton abundance and community composition in the eutrophic Jagst River followed a characteristic annual succession with a peak in April/May and a second peak in August similar to that generally reported for lakes (Wetzel 2001;Sommer et al 2012) and some rivers (Minaudo et al 2015). Therefore, phytoplankton community succession and individual species abundance in the River Jagst seems to be controlled by seasonal nutrient availability, physical conditions, and species competition as well as grazing as reported for other freshwater ecosystems in general (Sommer et al 2012;Meunier et al 2017).…”
Section: Potential Direct Effects Of the N Pulsesupporting
confidence: 78%
See 1 more Smart Citation
“…Our long-term data showed that the phytoplankton abundance and community composition in the eutrophic Jagst River followed a characteristic annual succession with a peak in April/May and a second peak in August similar to that generally reported for lakes (Wetzel 2001;Sommer et al 2012) and some rivers (Minaudo et al 2015). Therefore, phytoplankton community succession and individual species abundance in the River Jagst seems to be controlled by seasonal nutrient availability, physical conditions, and species competition as well as grazing as reported for other freshwater ecosystems in general (Sommer et al 2012;Meunier et al 2017).…”
Section: Potential Direct Effects Of the N Pulsesupporting
confidence: 78%
“…This may explain why individual eukaryote species in the Jagst River responded differently to the N pulse. Spring bloom communities were dominated by small‐celled taxa ( Stephanodiscus , Chlamydomonas , Cyclostephanos ), presumably with high growth rates (r‐strategy) and high nutrient affinity but low protection against grazing (Meunier et al ). In contrast, the more diverse phytoplankton community composition in summer primarily contained species with larger cell size or colony‐forming species ( Coelastrum , Cryptomonas , Scenedesmus , Nitzschia ) that likely possessed low growth rates but had nutrient storage capacity and grazing protection (K‐strategy) in addition to some fast‐growing species such as Chlamydomonas and Cyclotella .…”
Section: Discussionmentioning
confidence: 99%
“…, Meunier et al. ). This also allows us to establish relationships between observed shifts in ecosystem N:P medium (water or soil) with the shift in species dominance or community and/or in trophic web composition and structure.…”
Section: The Biogeochemical Niche Hypothesis and Related Approachesmentioning
confidence: 98%
“…Instead, all the organisms, independently of their taxonomical groups, are constituted by the same basic bio-elements, thus providing a general and easy to measure variable, the elementome, with which to establish the species-specific niche in plants , in animals (Gonz alez et al 2017), and in sets of plants and animals analyzed altogether (Bartrons et al 2018). The use of organismal elemental stoichiometry has been proven to be related to the species functional traits in aquatic and terrestrial ecosystems (Sardans et al 2012c, Meunier et al 2017. This also allows us to establish relationships between observed shifts in ecosystem N:P medium (water or soil) with the shift in species dominance or community and/or in trophic web composition and structure.…”
Section: The Biogeochemical Niche Hypothesis and Related Approachesmentioning
confidence: 99%
“…Theory linking functional diversity to ecosystem structure and function has historically focused on functional diversity of primary producers (Litchman, Klausmeier, Schofield, & Falkowski, 2007;Tilman, 1999;Violle et al, 2007), but trait-based models have also been used effectively to predict responses to varying functional diversity at higher trophic levels (Barnett, Finlay, & Beisner, 2007;Hébert, Beisner, & Maranger, 2016a;Hulot, Lacroix, Lescher-Moutoue, & Loreau, 2000;Lefcheck & Duffy, 2015). Many stoichiometric traits vary predictably over biologically relevant environmental gradients, and the functional importance of these traits has been well-documented (Hébert, Beisner, & Maranger, 2016b); as a result, trait-based approaches offer a powerful link between organisms and ecosystem function (Carmona, de Bello, Mason, & Lepš, 2016;González, Dézerald, Marquet, Romero, & Srivastava, 2017;Meunier et al, 2017). While this approach has been used to examine nutrient acquisition traits (Frost, Evans-White, Finkel, Jensen, & Matzek, 2005), it has not been widely applied to study functional variation in consumer taxa among ecosystems.…”
Section: Introductionmentioning
confidence: 99%